Community Empowerment Communication Strategy through CSR: A Case Study of the Canting Emas Batik Training - Desy Rahmawaty; Noor Khalida Maghfirah; Richard Saputra Adiguna (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the communication strategies of community empowerment implemented through the Corporate Social Responsibility (CSR) program of PetroChina International Jabung Ltd in the form of the Batik Canting Emas Training. This program represents an enabling CSR initiative focusing on enhancing community capacity and fostering women’s economic independence in Tanjung Jabung Barat Regency. The research was conducted from January to June 2025, with a three-month data collection period, thereby providing a contextual overview relevant to the socio-economic conditions of the local community. Using a descriptive qualitative approach, the study examines the communication strategies applied in the processes of awareness-building, training, and community assistance. The findings reveal that dialogical communication, interpersonal communication, and participatory approaches constitute the primary strategies in developing awareness, skills, and entrepreneurial motivation among local women. The contribution of this research lies in mapping CSR communication strategies that can serve as a practical reference for other companies in designing community-based empowerment programs. Moreover, the study highlights the added value of women’s empowerment, which not only promotes economic independence but also strengthens their social roles within families and communities. These strategies have proven to significantly contribute to creating a positive corporate image while reinforcing social relations between the company, the government, and the community.